An active learning approach for clustering single-cell RNA-seq data - Lin, Xiang; Liu, Haoran; Wei, Zhi; Roy, Senjuti Basu; Gao, Nan (Laboratory investigation, 2022)
Single-cell RNA sequencing (scRNA-seq) data has been widely used to profile cellular heterogeneities with a high-resolution picture. Clustering analysis is a crucial step of scRNA-seq data analysis because it provides a chance to identify and uncover undiscovered cell types. Most methods for clustering scRNA-seq data use an unsupervised learning strategy. Since the clustering step is separated from the cell annotation and labeling step, it is not uncommon for a totally exotic clustering with poor biological interpretability to be generated—a result generally undesired by biologists. To solve this problem, we proposed an active learning (AL) framework for clustering scRNA-seq data. The AL model employed a learning algorithm that can actively query biologists for labels, and this manual labeling is expected to be applied to only a subset of cells. To develop an optimal active learning approach, we explored several key parameters of the AL model in the experiments with four real scRNA-seq datasets. We demonstrate that the proposed AL model outperformed state-of-the-art unsupervised clustering methods with less than 1000 labeled cells. Therefore, we conclude that AL model is a promising tool for clustering scRNA-seq data that allows us to achieve a superior performance effectively and efficiently. Active learning (AL) model is a framework designed for single-cell RNA sequence (scRNA-seq) clustering. This model requires that the researchers label a small number of cells selected by a sample selection algorithm. The labeled cells are then used for the supervision of the clustering, to significantly boost the clustering performance of scRNA-seq.